USING THE VARIABLE SUBSTITUTION METHOD WHEN SOLVING SOME FOURTHORDER EQUATIONS - O. Makhmudova (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides theoretical information about the use of the method of substitution of variables in solving some fourth-order equations. Examples of these substitutions are shown below.